THE INFLUENCE OF AGE ON BEHAVIOR AND KNOWLEDGE OF MEDICAL MASKS WASTE MANAGEMENT DURING THE COVID-19 PANDEMIC - Susetiyo, Karindra Amadea; Syahbani, Primadita; Puteri, Astrid Aulia Artiono; Rossyanti, Lynda (Journal of Community Medicine and Public Health Research, 2022)
The use of masks as self-protection from Covid-19 can cause new problems by increasing the amount of waste. Medical masks are infectious waste containing microplastics that are difficult to decompose. People's behavior and level of knowledge may have a role in the management of medical mask waste. Therefore, this research aimed to find out the comparison of the age group <17 years and 18-25 years regarding the knowledge about the impact of medical masks on the environment as an indication of public concern for environmental preservation. The research was an analytic observational study. The sample was selected using total sampling according to age group. The variables studied were the management of medical masks and respondents' knowledge of the impact of medical masks on the environment as measured from questionnaire data. The data obtained were tested using the independent sample t-test and the Chi-Square test. The results obtained a p-value=0.259 related to the management of medical masks and  p-value=0.172 related to knowledge of the impact of medical mask waste. There was no relationship between the age group <17 years and 18-25 years related to the management of medical masks and knowledge of the impact of mask waste on the environment.